The Comparison Models of Earning Management, CSR, and Intellectual Capital on Firm Value Moderated by Performance - Rilla Gantino; Endang Ruswanti; Agung Mulyo Widodo; Deni Iskandar (Journal of Accounting Research, Organization and Economics, 2022)
Objective – This study aims to compare the effect of earnings management, corporate social responsibility (CSR), and intellectual capital on firm value moderated by performance in two different periods, 2015-2019 (before COVID-19 pandemic) and 2015-2020 (9 months of pandemic).Design/methodology – This Study used two data year groups, from 2015-2019 and 2015-2020 with purposive sampling technique. The population of 5 sectors and 2 sub-sectors of companies listed on the Indonesia Stock Exchange which consists of basic and chemical industry, consumer goods, mining, Infrastructure, Utilities Transportation, various industries (excluding textile and automotive) sector and the Automotive Components, Textile Garment sub-sector.Results – The results show, even though the pandemic lasted 9 months in 2020, the average return on assets (ROA) of the 2015-2020 group decreased, turns out it doesn't have much effect on the strength of ROA to moderate the variable x to y. For 2015-2019 (before COVID-19 pandemic), performance moderates the effect of earnings management, CSR, and intellectual capital on firm value in the textile, automotive and components sub-sectors, various industries, consumer goods sectors and infrastructure and for 2015-2020 (9 months of the pandemic) only textile, automotive and components sub-sectors, various industries, and infrastructure. Partially for 2015-2019, value added intellectual coefficient (VAIC) has a significant effect moderated by performance in the consumer goods infrastructure sector, and automotive, then CSR has a significant effect moderated by performance in the basic industry and textile. Earning management has a significant effect moderated by performance in the basic industry, infrastructure and automotive. The same results for 2015-2020, for earning management. VAIC has a significant effect moderated by performance in consumer goods and infrastructure sector and CSR has a significant effect moderated by performance in textile, basic industry and various industries.Research limitations/implications – This study only uses secondary data for 2015-2019 and 2015-2020 and only uses 5 sectors from 9 sectors and does not compare each sub-sector.Novelty/Originality – This study obtained a comparison of the model of the influence of earnings management, intellectual capital, and CSR on firm value moderated by performance for 5 sectors and 2 sub-sectors.